2020
DOI: 10.14447/jnmes.v23i1.a01
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Effect of LiMn2O4, Nanofibers of LiMn2O4, and Graphene/Polyaniline/Carbon Nanotube as Electrode Materials in the Fuel Cell

Abstract: This study is conducted to explore the best electrodes materials for energy conversion devices. The two cathode materials (LiMn2O4 and nanofibers of LiMn2O4) and the anode material (graphene/polyaniline/carbon-nanotube) were synthesized by a wet chemical method which includes sol-gel and chemical polymerization techniques. The prepared materials were characterized by SEM, XRD FTIR, and cyclic voltammetry. The characterization results show that LiMn2O4 exhibits a porous and hollow structure, which improves the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In Figure 3 b), the spectra of the calcined monolith before and after the generation of vacancies using HCl were observed. Particularly, the band at 556 cm −1 has been assigned to ν ${\nu }$ LiO mode of LiO 4 , [32] which was observed in the M spectrum but is no longer visible in the MH sample. It has been reported that the aforesaid discrepancy is related to an exchange between Li + and H + [33] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 3 b), the spectra of the calcined monolith before and after the generation of vacancies using HCl were observed. Particularly, the band at 556 cm −1 has been assigned to ν ${\nu }$ LiO mode of LiO 4 , [32] which was observed in the M spectrum but is no longer visible in the MH sample. It has been reported that the aforesaid discrepancy is related to an exchange between Li + and H + [33] .…”
Section: Resultsmentioning
confidence: 99%
“…Also, the d‐spacing was calculated using the Bragg's Law: [32] d=nλ2*sinθ $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr d={{n\lambda }\over{2^{\ast}{\rm sin}{\rm \theta }}}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic concept of using sulfur-based functional groups is to create a diverse polymer with desired properties. Currently, the pivot of researchers is to enhance the materials’ properties and characterization by sulfur introduction into the main chain to comprehend the applications. …”
Section: Introductionmentioning
confidence: 99%